The relationship between basic sanitation and diarrhea incidence in toddlers in the working area of the Pamandati Public Health Center - Selvi Safitri; Jafriati Jafriati; Siti Rabbani Karimuna (Indonesian Journal of Health Science, 2026)
Diarrhea remains a significant public health problem in Indonesia and is still frequently found in many regions with relatively high mortality rates, particularly among children under five years of age. Toddlers are the most vulnerable group to diarrhea, and this condition can lead to death if it is not treated promptly and appropriately. The occurrence of diarrhea in toddlers can be influenced by various factors, one of which is inadequate environmental sanitation. This research aims to analyze the relationship between basic sanitation and the incidence of diarrhea among toddlers in the working area of Pamandati Community Health Center, South Konawe Regency, in 2026. This research employed an analytical survey with a cros sectional design. The sample consisted of 89 partisipants selected using proportional random sampling. Data were collected through observation and interviews using a questionnaire, and were analyzed using univariate and bivariate analysis. The results of the statistical analysis at a significance level of α = 0.05 indicated that there was a relationship between clean water facilities (p-value = 0.001) and healthy latrine facilities (p-value = 0.036) with the incidence of diarrhea among toddlers. Meanwhile, waste disposal facilities (p-value = 0.389) and wastewater drainage systems (p-value = 0.082) showed no association with the incidence of diarrhea. In conclusion, the availability of clean water facilities and healthy latrines is associated with the incidence of diarrhea among toddlers in the working area of Pamandati Community Health Center in 2026.